Droplet-Microfluidic-Based Promoter Engineering and Expression Fine-Tuning for Improved Erythromycin Production in Saccharopolyspora erythraea NRRL 23338 - Yun, Kaiyue; Zhang, Yue; Li, Shixin; Wang, Yan; Tu, Ran; Liu, Hao; Wang, Meng (Frontiers in Bioengineering and Biotechnology, 2022)
Erythromycin is a clinically important drug produced by the rare actinomycete Saccharopolyspora erythraea. In the wide-type erythromycin producer S. erythraea NRRL 23338, there is a lack of systematical method for promoter engineering as well as a well-characterized promoter panel for comprehensive metabolic engineering. Here we demonstrated a systematical promoter acquiring process including promoter characterization, engineering and high-throughput screening by the droplet-microfluidic based platform in S. erythraea NRRL 23338, and rapidly obtained a panel of promoters with 21.5-fold strength variation for expression fine-tuning in the native host. By comparative qRT-PCR of S. erythraea NRRL 23338 and a high-producing strain S0, potential limiting enzymes were identified and overexpressed individually using two screened synthetic promoters. As a result, erythromycin production in the native host was improved by as high as 137.24 folds by combinational gene overexpression. This work enriches the accessible regulatory elements in the important erythromycin-producing strain S. erythraea NRRL 23338, and also provides a rapid and systematic research paradigm of promoter engineering and expression fine-tuning in the similar filamentous actinomycete hosts.